Risk assessment of water resource shortages in the Aksu River basin of northwest China under climate change. (1st March 2022) - Yang, Peng; Zhang, Shengqing; Xia, Jun; Chen, Yaning; Zhang, Yongyong; Cai, Wei; Wang, Wenyu; Wang, Huaijun; Luo, Xiangang; Chen, Xi
Abstract: As most of the runoff resulting from snow-ice melt is related to climate change factors in the arid region of northwest China, the risk to water resource systems threatens the socio-economic and ecological environment and is becoming increasingly prevalent. Therefore, we explored the risks of water resource shortages for different periods (2010, 2020, and 2030) in the Aksu River basin (ARB) in the northwest arid region of China by reconstructing a risk model based on the framework proposed by the Intergovernmental Panel on Climate Change (IPCC) with an improved vulnerability (V) module and a more suitable hazard probability in the cost module. The major conclusions are as follows: (1) the simulation of the Community Land Model-Distributed Time Variant Gain Model (CLM-DTVGM) and the Vegetation Interface Processes model (VIP) was suitable for the eco-hydrological processes in the ARB under climate change (i.e., R 2  ≥ 0.583; Nash coefficient ≥0.371; and relative mean standard ≤155.727 for CLM-DTVGM; R 2  = 0.798 for VIP); (2) the vulnerability of the water resource system in the ARB was medium in 2010, and dropped to a medium-low to non-vulnerable level in 2020 before increasing in 2030 under different Representative Concentration Pathways (RCP) (RCP2.6, RCP4.5, and RCP8.5); and (3) there was a medium-low risk of water resource shortages in the ARB in 2010 (i.e., 0.246), and although the risk of water resource shortages decreased in 2020 due to the increasing water supply from mountainous areas, the risk predicted to increase significantly in 2030, to a medium-high risk level. This study is critical for accurately predicting and understanding the impact of climate change on water resource systems as well as on the drought risk in arid regions. Graphical abstract: Image 1 Highlights: Climate change and human activities have a significant impact on the risk of water shortage in the Aksu River Basin. VIP and CLM-DTVGM can simulate the hydrological process in the Aksu River Basin well. The cost of drought disaster was well integrated into the risk assessment model of water resource system. The resilience of the water resource system in the ARB weakened, but the cost and exposure, and vulnerability increased. The water resource system of Aksu River Basin will also suffer from great risks in the future.